Penerapan Metode Talaqqi Pada Siswa Tingkat Sekolah Dasar - Abdullah, Tengku Muhammad Amir Yusuf; Arsalan, Syakib; Ramadhani, Raffi Fahrezi; Basyri, Lalu Zaedan; Murtadha, Muhammad Hafidz; Alharitsi, Naufal Adi (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2025)
This journal examines a community service program initiated by the KKN Team 2 of STIQ Zad Cianjur, focusing on religious and educational development—specifically, the instruction of Qur’anic reading using the Talaqqi method. At the elementary school level in Indonesia, particularly in the Cianjur Regency, Qur’an reading education continues to face significant challenges, especially regarding the correct articulation of Arabic phonemes (makhārijul ḥurūf) and the application of tajwid rules. Talaqqi is a traditional pedagogical approach in which the student reads directly in front of the teacher, who then immediately corrects any errors in pronunciation and recitation, This study aims to assess the effectiveness of the Talaqqi method in addressing these issues. Utilizing a qualitative approach and classroom action research, the study was conducted with students from SDN Cibeureum and Madrasah DTA Shobirunnajah, located in Cibeureum Village, Cianjur Regency, West Java. The findings reveal that the consistent implementation of the Talaqqi method significantly improves students’ ability to read the Qur’an. The direct, auditory, and mimetic nature of this method fosters a deeper understanding of both correct pronunciation and the principles of tajwid.